Use of adaptive system of redistribution engine capacities on purpose decrease in the harmful impacts of toxic substances on the human body - D. S. Aleshko; M. V. Sukovin; V. V. Stolyarov (Вестник СибАДИ)
The article is devoted to the problem of reducing the harmful effects of toxic substances on the human body in the work of the chain trench excavator. Typical load variation on the shaft of the diesel internal combustion engine during the working process associated with changes of soil conditions leads to increased content in the exhaust gases of carbon monoxide, nitrogen oxides, soot. The article describes a method that allows the engine to operate at rated speed. By fixing the nominal mode, optimal redistribution of engine power between the working body and the mover, it is possible to achieve maximum combustion of the fuel, resulting in reduction of harmful gases.